Assessment of effect of osteoarthritis of knee on the activities of daily living and treatment seeking behaviour of patients at Kalaburagi, Gulbarga city of Karnataka - Reshmi, Panchasheela S.; Bhavsar, Sudip V. (International Journal Of Community Medicine And Public Health, 2020)
Background: Osteoarthritis (OA) is estimated to be the fourth leading cause of disability in most of the countries. It is the most frequent joint disease with a prevalence of 22% to 39% in India. The objectives of the study were to assess the effect of OA of knee on activities of daily living using Western Ontario and McMasters University Osteoarthritis (WOMAC) index and treatment seeking behaviour of patient with OA of knee. Methods: Convenience sampling was used to find out patients of OA from 15th April to 1st June 2016 with cross-section type of study design. Data was collected and analyzed using MS Excel 2000. Results: In this study 16% of participants in underweight category and 79% participants in overweight category reported moderate to very severe pain on visual analogue score (VAS). Treatment seeking behaviour was quite poor in lower socio-economic class (SEC) as compared to upper SEC. 20.34% participants had extreme pain while walking. 9.74% participants experienced extreme level of morning stiffness while 18.72% had extreme difficulty while ascending stairs. 14.87% experienced extreme difficulty during getting standing position from sitting position. Conclusions: Moderate to severe pain on VAS was more common in overweight group compared to underweight group. Treatment seeking behaviour was quite poor in lower SEC as compared to upper SEC. 20.34% participants had extreme pain while walking. 14.87% experienced extreme difficulty during getting standing position from sitting position.